Dance for Me When I Die - Alarcón, Cristian, 1970- (Book collections on Project MUSE., 2019)
In Dance for Me When I Die--first published in Argentina in 2004 and appearing here in English for the first time--Cristian Alarcón tells the story and legacy of seventeen year old Víctor Manuel Vital, aka Frente, who was killed by police in the slums of Buenos Aires.